Effect of computed tomography perfusion post-processing algorithms on optimal threshold selection for final infarct volume prediction. Issue 4 (August 2020) - Rava, Ryan A; Snyder, Kenneth V; Mokin, Maxim; Waqas, Muhammad; Allman, Ariana B; Senko, Jillian L; Podgorsak, Alexander R; Bhurwani, Mohammad Mahdi Shiraz; Davies, Jason M; Levy, Elad I; Siddiqui, Adnan H; Ionita, Ciprian N
In acute ischemic stroke (AIS) patients, eligibility for endovascular intervention is commonly determined through computed tomography perfusion (CTP) analysis by quantifying ischemic tissue using perfusion parameter thresholds. However, thresholds are not uniform across all analysis methods due to dependencies on patient demographics and computational algorithms. This study aimed to investigate optimal perfusion thresholds for quantifying infarct and penumbra volumes using two post-processing CTP algorithms: Vitrea Bayesian and singular value decomposition plus (SVD+). We utilized 107 AIS patients (67 non-intervention patients and 40 successful reperfusion of thrombolysis in cerebral infarction (2b/3) patients). Infarct volumes were predicted for both post-processing algorithms through contralateral hemisphere comparisons using absolute time-to-peak (TTP) and relative regional cerebral blood volume (rCBV) thresholds ranging from +2.8 seconds to +9.3 seconds and –0.23 to –0.56 respectively. Optimal thresholds were determined by minimizing differences between predicted CTP and 24-hour fluid-attenuation inversion recovery magnetic resonance imaging infarct. Optimal thresholds were tested on 60 validation patients (30 intervention and 30 non-intervention) and compared using RAPID CTP software. Among the 67 non-intervention and 40 intervention patients, the following optimal thresholds were determined: intervention Bayesian: TTP = +4.8 seconds, rCBV = –0.29; intervention SVD+: TTP = +5.8 seconds, rCBV = –0.29; non-intervention Bayesian: TTP = +5.3 seconds, rCBV = –0.32; non-intervention SVD+: TTP = +6.3 seconds, rCBV = –0.26. When comparing SVD+ and Bayesian post-processing algorithms, optimal thresholds for TTP were significantly different for intervention and non-intervention patients. rCBV optimal thresholds were equal for intervention patients and significantly different for non-intervention patients. Comparison with commercially utilized software indicated similar performance.